Validation of RFLP-Combined PCR Technique to Detect Porcine Contamination in Meatball (Halal Analysis) - Raharjo, Tri Joko; Sismindari, Sismindari (2010)
Porcine contamination was one important issue in food certification for Halal. Here, we reported PCR combined with RFLP technique to detect porcine contamination in meatball. Various concentration of pork was added to beef in preparation of the meatball. Mithocondrial DNA was then isolated from the meatball followed by PCR using published primers that amplified cytB gene. A + 350 bp DNA fragment was resulted from PCR. PCR product was targeted for digestion by means of BamHI and BseDI enzymes. Since these enzymes cut porcine cytB gene but does not cut beef cytB gene, all meatball contain porcine contamination give small DNA fragment (+ 220 and 130 bp) in electrophoresis analysis, while the absent of these DNA fragment leading to conclusion that meatball sample free from porcine. This method has been validated to detect up to 1% of porcine present in the meatball.